Analisis Framming Editorial Terkait Pembangunan Ibukota Nusantara : ”Soal IKN, Biar Prabowo yang Putuskan” pada Media The Jakarta Post - Patricia Sihotang (Institut Nalanda, 2025)
The editorial titled “Soal IKN, biar Prabowo yang putuskan” from The Jakarta Post discusses the development of the Nusantara capital (IKN), emphasizing that this process should be conducted calmly, with focus and without haste. The study employs Pan and Kosicki's framing analysis to examine the narrative structure of the editorial text, concentrating on syntactic, script, thematic, and rhetorical elements. The analysis reveals that the editorial frames the national issue of capital city development, highlighting the challenges, conflicts of interest, and the necessity for strategic planning. Full trust is placed in Prabowo Subianto, the elected president for the 2024-2029 period, to continue the IKN development project. The editorial also sharply criticizes the previous president for rushing through the implementation of programs. Arguments are presented with logical reasoning, accompanied by hopes for the future of IKN.